2019
DOI: 10.3846/mla.2019.9583
|View full text |Cite
|
Sign up to set email alerts
|

Žaliosios Ekonomikos Probleminės Sritys Globalioje Rinkoje / Green Economy Problem Areas in the Global Market

Abstract: The objective is to highlight the main problem areas of the green economy in the global market, based on international proposals from the international organizations for the green economy, research on raw materials and empirical data. Research methods applied: scientific literature analysis, systematization, comparative analysis, generalization. The results of the survey allowed to highlight the main areas of the green economy. It presents the concept and development of the green economy, and identifies key ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This attitude is confirmed by Razauskas (2009), who states that ensuring sustainability should be a dynamic process, assessing the balance between different groups of society and society and nature, taking into account future perspectives. Definitely, this public attitude directly influences the behavior of business entities and organizations, thus forming a green economy, which, according to Alekna and Kazlauskienė (2019), is considered as a tool for achieving sustainable development. Alekna and Kazlauskienė (2019) emphasize that the green economy is a type of economy that is oriented towards the creation of economic welfare that has minimal or no impact on nature.…”
Section: Contextual Background For Analysis Of the Green Organizationmentioning
confidence: 99%
See 2 more Smart Citations
“…This attitude is confirmed by Razauskas (2009), who states that ensuring sustainability should be a dynamic process, assessing the balance between different groups of society and society and nature, taking into account future perspectives. Definitely, this public attitude directly influences the behavior of business entities and organizations, thus forming a green economy, which, according to Alekna and Kazlauskienė (2019), is considered as a tool for achieving sustainable development. Alekna and Kazlauskienė (2019) emphasize that the green economy is a type of economy that is oriented towards the creation of economic welfare that has minimal or no impact on nature.…”
Section: Contextual Background For Analysis Of the Green Organizationmentioning
confidence: 99%
“…Definitely, this public attitude directly influences the behavior of business entities and organizations, thus forming a green economy, which, according to Alekna and Kazlauskienė (2019), is considered as a tool for achieving sustainable development. Alekna and Kazlauskienė (2019) emphasize that the green economy is a type of economy that is oriented towards the creation of economic welfare that has minimal or no impact on nature.…”
Section: Contextual Background For Analysis Of the Green Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The green economy could be a means of implementing sustainable development ideas that are related to nature conservation. After reviewing and analysing the scientific literature, it was found that the green economy is a type of economy that focuses on the creation of economic wellbeing, and that has minimal or no impact on nature (Alekna & Kazlauskienė, 2019;Augustaitė, 2020). Green economy can be a tool to achieve sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…The first group assesses tangible resources (subgroups: physical and financial), and the second groupintangible resources (subgroups: human, technological, and organizational). Statements to be evaluated for each evaluated component are formulated based on the results of the theoretical research (Zakarevičius, 2010;Mackevičius & Daujotaitė, 2011;Inderst et al, 2012;Alekna & Kazlauskienė, 2019;Barno, 2021;Wang et al, 2021;Khan et al, 2021;Debrah et al, 2022;Maletič et al, 2020;Jancenelle, 2021;Abideen et al, 2022;Tang et al, 2018;Roscoe et al, 2019;Singh et al, 2020;Aboramadan & Karatepe, 2021;Bose & Luo, 2012;Chuang & Huang, 2015;Su et al, 2020, etc.). In total, 54 statements are proposed to be evaluated; the maximum rating according to the Likert scale is five points, and the maximum sum of all assigned scores is equal to 270 points.…”
Section: Theoretical Aspects Of An Organization's Performance Evaluat...mentioning
confidence: 99%